Legumes in dry areas - Kumar, D.; Henry, A.; Vittal, K. P. R. (Indian Arid Legumes Society/ Scientific Publishers (India), 2009)
Papers presented at the 3rd Symposium on Arid Legumes, held at Jodhpur during 28-30 June 2008.